The Landscape of Coronavirus Disease 2019 (COVID-19) and Integrated Analysis SARS-CoV-2 Receptors and Potential Inhibitors in Lung Adenocarcinoma Patients - Tang, Bufu; Zhu, Jinyu; Cong, Ying; Yang, Weibin; Kong, Chunli; Chen, Weiyue; Wang, Yajie; Zeng, Yong; Ji, Jiansong (Frontiers in Cell and Developmental Biology, 2020)
The outbreak of novel coronavirus disease 2019 (COVID-19) has become the largest health threat worldwide, with more than 9.08 million positive cases and over 470,000 deaths confirmed. In this study, we confirmed that significantly differentially expressed genes in COVID-19 patients were mainly involved in the regulation of immune and inflammation-related signaling pathways. It is worth noting that many infected COVID-19 patients have malignant tumors, and their prognosis is poor. To explore the susceptibility factors of cancer patients, we assessed the expression of ACE2, TMPRSS2 and the endocytic regulator AAK1 in lung adenocarcinoma (LUAD) patients and explored their effects on immune infiltration. We found that the expression of ACE2 and TMPRSS2 in LUAD patients was significantly increased, and the high-expression genes led to decreased infiltration of immune cells such as CD4+ and CD8+ T cells, which may explain why LUAD patients are susceptible to SARS-CoV-2 and present serious clinical manifestations. In addition, we also identified miR-432-5p as a potential targeted molecule and bexarotene as a potential targeted drug of the three genes through bioinformatic analysis and further verified the anti-inflammatory effect of bexarotene, providing new ideas for the treatment of COVID-19.